Improved photoelectrochemical water splitting of hematite nanorods thermally grown on Fe–Ti alloys - Wang, Lei; Lee, Chong-Yong; Schmuki, Patrik (Electrochemistry Communications, 2014)
Here we show that hematite ( extgreeka-Fe2O3) nanostructures with a high water splitting performance can be formed on Fe–Ti alloys using the most simple thermal treatment in air and Ar. The use of the Fe–Ti alloy suppresses the formation of thick suboxide underlayers that are strongly detrimental for the photoconversion efficiency. The formed nanorod structures show an onset potential of up to 0.6–0.7 VRHE. This beneficial effect is attributed to the combination of suppression of a thick suboxide and the nature of the extgreeka-Fe2O3 nanorods after Ar annealing.
EAM Import::2019-03-13